EXPERIMENTAL STUDY OF NUCLEATE POOL BOILING WITH WATER IN ATMOSPHERIC PRESSURE - Agma, Onur; Yildiz, Sebiha (VINCA INST NUCLEAR SCI, 2024)
This study experimentally investigated nucleate pool boiling heat transfer for a polished copper surface and water fluid couple under atmospheric pressure. The results were compared with the correlations in the literature. The experimental results were compared with the surface -liquid correlation constants Rohsenow, Pioro, Vachon, Griffith, and Das used for the temperature exceedance values. When the results of Griffith's correlation constant were compared with the experimental values, it was seen that it was the most appropriate correlation compared to other correlations, with a minimum and maximum error of 0.4-12%. In addition, Forster-Zuber, Pioro, Kutateladze old, Kutateladze new, Kruzhilin, and Cooper correlations were compared with experimental results regarding the heat transfer coefficient. Compared with the correlation proposed by Pioro for the heat transfer coefficient, it was calculated as the most suitable correlation with a minimum and maximum difference of 0.2-8%.
Keywords: nucleate pool boiling; water; polished copper; atmospheric pressure; HEAT-TRANSFER ENHANCEMENT; CRISIS PHENOMENON; CONSTANTS; DYNAMICS; Thermodynamics